2014
DOI: 10.5539/ijef.v6n6p234
|View full text |Cite
|
Sign up to set email alerts
|

Cost Management Practices and Firm’s Performance of Manufacturing Organizations

Abstract: This study investigates the relationship that exists between cost management practices and firm's performance in the manufacturing organizations using data from 40 manufacturing companies listed on the Nigeria stock exchange during the period of 2003 to 2012. Four hypotheses were formulated for the study and tested using t-statistic. The study relied on secondary data extracted from the audited financial statement of the selected companies. Direct material cost, direct labour cost, production overhead cost and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…In connection with the managerial decision making, there exists another differentiation of cost groups, which are known as controllable and non-controllable costs. As Oluwagbemiga et al (2014) mentioned a controllable cost is any cost which is under the direct influence of a responsible manager for a given time period. It is suggested that the costs and revenue must be related to individual who is responsible for their incurrence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In connection with the managerial decision making, there exists another differentiation of cost groups, which are known as controllable and non-controllable costs. As Oluwagbemiga et al (2014) mentioned a controllable cost is any cost which is under the direct influence of a responsible manager for a given time period. It is suggested that the costs and revenue must be related to individual who is responsible for their incurrence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…">IntroductionCost effectiveness can lead to rapid improvement of firm's financial performance (Kinyugo, 2014;Liu, Wu, Zyong and Liu, 2020). There exists a direct relationship between effective management of direct and indirect costs and profitability of listed non-financial firms in Nigeria (Oluwagbemiga, Olugbenga and Adeoluwa, 2014;Okezie, Okezie and Ogbu, 2017). However, overhead expenses are either affected by fluctuations in the volume of productions or sales activities (direct/variable overhead) or otherwise (fixed overhead).…”
mentioning
confidence: 99%
“…The second standpoint considers the consequences of overstaffing on the performance of the joint venture. Generally, the primary goal of business is the economic profit, secondary goals are also pursued without obstructing the main one (Oluwagbemiga, Olugbenga and Zaccheaus, 2014). Creating jobs is a reasonable goal for the Egyptian government, however, this goal now has occupied their first priorities.…”
Section: Parent Firm -Country Finance Manager (P Hh)mentioning
confidence: 99%
“…Creating jobs is a reasonable goal for the Egyptian government, however, this goal now has occupied their first priorities. From a costefficiency point of view, managing a company with proper cost structure elevates its profitability and performance (Oluwagbemiga et al, 2014). According to Horngren, Datar, Foster, Rajan and Ittner (2009), costs are variable and fixed based on the activity and size of the business.…”
Section: Parent Firm -Country Finance Manager (P Hh)mentioning
confidence: 99%
See 1 more Smart Citation